THE EFFECT OF BRAND IMAGE, PERCEIVED PRCE, AND PERCEIVED QUALITY ON CONSUMERS’ PURCHASE DECISION OF POND’S SKIN CARE PRODUCT - Cahyani, Nidia Sri; Lapian, S L.H.V.J; Tumiwa, Johan (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract:Beauty has been one of the important things for women. Nowadays, the use of skin care such as mouisturizer have become their daily routines, some of them are use skin care products from beauty clinics also use products that sale in the supermarket. The aims of this study are to analyze the effect  of brand image, perceived price, and perceived quality on consumers’ purchase decision of Pond’s skin care product. This reserach is causal type of research which uses primary data obtained through questionnaires and uses Ordinal Regression Analysis. The population observed is people in Manado who have used Pond’s skin care product with 100 respondents as the sample size. The result of this study shows that brand image, perceived price, and perceived quality have significant effects on consumers’ purchase decision. For recommendations, the company must keep maintaining and improve their brand image, price, and the quality of produc Pond’s.Keywords:brand image, perceivedprice, perceived quality, consumer purchase decision